2012 International Conference on Cloud Computing Technologies, Applications and Management (ICCCTAM) 2012
DOI: 10.1109/iccctam.2012.6488085
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of Cloud Computing adoption on organizational flexibility: A client perspective

Abstract: Today's turbulent business environment poses a challenge of survival for all organizations. Flexibility to adapt to these changes is the key to success. Role of Information Technology innovations like Cloud Computing cannot be denied in achieving organizational flexibility. Introduction of cloud computing has changed the manner in which

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 21 publications
0
40
0
2
Order By: Relevance
“…If a user feels at risk, they would tend to choose a credible supplier. Bharadwaj and Lal (2012) found that vendor credibility has a positive influence on adoption of cloud computing through a case study (Bharadwaj & Lal, 2012). Furthermore, Heart (2010) found that vendor credibility has a positive impact on SaaS adoption intention and a negative impact on perceived risk (Heart, 2010).…”
Section: Perceived Risk and Perceived Trustmentioning
confidence: 99%
“…If a user feels at risk, they would tend to choose a credible supplier. Bharadwaj and Lal (2012) found that vendor credibility has a positive influence on adoption of cloud computing through a case study (Bharadwaj & Lal, 2012). Furthermore, Heart (2010) found that vendor credibility has a positive impact on SaaS adoption intention and a negative impact on perceived risk (Heart, 2010).…”
Section: Perceived Risk and Perceived Trustmentioning
confidence: 99%
“…13,14 Studies are available that have investigated the factors influencing the successful adoption of cloud technology in the health sector 12,[15][16][17] as well as in other sectors. [18][19][20][21][22][23][24][25][26][27] Figure 1 shows that while there has been a significant increase in published articles on cloud technology adoption in the non-health sector, overall, there is a dearth of articles on the health sector.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, firms in the same industry tend to become homologous over time as customer, competitive, and other stakeholders' pressures influence them to copy other leaders in the same industry (Oliveira & Martins, 2011). Some recent studies have used INT for innovation adoption (Baptista, 2009;Bharadwaj & Lal, 2012;Hedman & Borell, 2004). Other studies have also combined the TOE framework with the INT (Soares-Aguiar & Palma-dos-Reis, 2008; Gibbs & Kraemer, 2004) and the DOI with INT (Bharati & Chaudhury, 2006).…”
Section: Technology-organization-environment Frameworkmentioning
confidence: 99%